PRODUCT DEVELOPMENT AND ELIGIBILITY ASSESSMENT OF PICTORIAL METAPLAN FOR INTERACTIVE ENGLISH TEACHING IN 8TH GRADE JUNIOR HIGH SCHOOL - Deswandito Dwi Saptanto; Tri Arie Bowo; Ratih Laily Nurjanah (PHILOSOPHICA Jurnal Bahasa, Sastra, dan Budaya, 2021)
This study focuses on the development of instructional media using pictorial metaplan and provide eligibility assessment for the product. The use of pictorial metaplan media aims to increase interest in learning vocabulary as well as to directly apply of English speaking practice to students of 8th grade Junior High School. This type of research is using Research and Development method (R&D). Direct trials was conducted on 1 media expert, 4 teachers and 7 students from 8th grade Junior High School. The implementation of the use of pictorial metaplan to the subjects of this study used a combination of the Total Physical Response (TPR) and Student-Centered Learning (SCR) methods. The results of this study are indicated by the total score of the product eligibility assessment that were obtained from the total conversion of the assessment from media expert, teachers and students. The total score of the media experts was 106, which meant in ‘very eligible’ category, the total score of the teacher was 81.6, which meant ‘eligible’ category and the total score of the students was 92.2, which meant ‘eligible’ category. Based on the results, pictorial metaplan is eligible to be a teaching aid for learning English, especially in speaking competence.